Indonesia Diplomacy for Achieving UNESCO Global Geopark (UGG) Status - Choirunnisa, Priyanka Inmas; Susilo, Djoko; Albayumi, Fuat (Rumah Jurnal UNEJ, 2022)
This study analyzes Indonesia diplomatic efforts to achieve UNESCO Global Geopark (UGG) status for geopark tourism sites in Indonesia. Through qualitative descriptive research with secondary data sources derived from literature study, this study aims to determine the steps related to development and management carried out by the Indonesian government to achieve UNESCO Global Geopark (UGG) status. To achieve this status, Indonesia is practicing diplomacy through the government track in accordance with the Diplomacy concept. The success of Indonesia’s government efforts in obtaining UNESCO Global Geopark (UGG) status for geopark tourism sites are in collaboration with stakeholders in tourism sector.